SENI RUPA "BIASA-BIASA SAJA" KARYA HERMAN "BENG" HANDOKO - Zarkasi, Much. Sofwan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2017)
ABSTRACTThe aim of the article entitled Seni Rupa â€œBiasa-Biasa Sajaâ€ Karya Herman â€œBengâ€ Handoko", is to understand creative and interpret the work of art aesthetics from Herman" Beng "Handoko or often called Beng Herman. This article is the result of qualitative research using Deteritorial theory Gilles Deleuze to understand Beng Herman's creative process. To understand the aesthetics of Beng Herman's work using the aesthetics of Clive Bell, inform art as a personal experience that presents a form of significance. Findings from this research are: (1) Beng Herman's art is present from a routine of feeling and thinking that frees himself from the boundaries outside himself so that his work is present from pure feelings from within him, (2) through liberation makes routine art activities become "mediocre" activities which are all responded to become a desire to produce aesthetic work, a depth of individual processes that display honesty without judgment on other individuals and (3) the aesthetics of Beng Herman's work is present from the unity of the line, fields that are coordinated freely, which sometimes appear repetitive by displaying dynamic rhythms. An ordinary thing that becomes extraordinary when something becomes a deep personal experience and presents diverse possibilities and meanings according to each individual's aesthetic experience.Â Keywords: Art, creative, Aesthetics, Beng Herman